2-Nonanone is a Critical Pheromone Component for Cerambycid Beetle Species Native to North and South America. Issue 3 (16th March 2021) - Silva, Weliton D; Hanks, Lawrence M; Mongold-Diers, Judith A; Grommes, Anna C; Bento, José Maurício S; Millar, Jocelyn G
Abstract: An increasing body of evidence indicates that cerambycid beetles native to different continents may share pheromone components, suggesting that these compounds arose as pheromone components early in the evolution of the family. Here, we describe the identification and field testing of the pheromone blends of two species in the subfamily Cerambycinae that share 2-nonanone as an important component of their male-produced aggregation-sex pheromones, the South American Stizocera consobrina Gounelle (tribe Elaphidiini) and the North American Heterachthes quadrimaculatus Haldeman (tribe Neoibidionini). Along with 2-nonanone, males of S. consobrina also produce 1-(1 H -pyrrol-2-yl)-1, 2-propanedione, whereas males of H. quadrimaculatus produce 10-methyldodecanol. Field bioassays conducted in Brazil (targeting S. consobrina ) and Illinois (targeting H. quadrimaculatus ) demonstrated that adults of both species were attracted only by the blends of both their pheromone components, and not to the individual components. The use of the pyrrole as a critical component for the former species is further evidence that this compound is a common pheromone structure among cerambycines in different biogeographical regions of the world.